1999
DOI: 10.1001/archpsyc.56.3.261
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Relationship Between Depressive Symptoms and Dementia

Abstract: Background:The temporal relationship between the appearance of depressive symptoms and the clinical onset of dementia and Alzheimer disease was evaluated in a community sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
209
1
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(222 citation statements)
references
References 51 publications
6
209
1
6
Order By: Relevance
“…In our study, six of nine patients with neurodegenerative disease had histories of latelife depressive symptoms. Depression is believed to be a risk factor for the onset of Alzheimer's disease (Green et al, 2003;Chen et al, 1999;Kokmen et al, 1991;Kral and Emery, 1989). Affective disorders are often comorbid with neurodegenerative disorders that are associated with dementia (Allen and Burns, 1995;Schreinzer et al, 2004;Lauterbauch et al, 2004).…”
Section: Possible Relevance Of 5-htt Axon Degeneration To Symptoms Ofmentioning
confidence: 99%
“…In our study, six of nine patients with neurodegenerative disease had histories of latelife depressive symptoms. Depression is believed to be a risk factor for the onset of Alzheimer's disease (Green et al, 2003;Chen et al, 1999;Kokmen et al, 1991;Kral and Emery, 1989). Affective disorders are often comorbid with neurodegenerative disorders that are associated with dementia (Allen and Burns, 1995;Schreinzer et al, 2004;Lauterbauch et al, 2004).…”
Section: Possible Relevance Of 5-htt Axon Degeneration To Symptoms Ofmentioning
confidence: 99%
“…A community based study in Australia found no association between baseline depression and the development of dementia 3-6 years later (Henderson et al, 1997). In a rural Pennsylvania based study, subjects with depression at the start of the study were were found to be at slightly higher risk for developing dementia (relative risk 1.27) on follow up, though the risk was not statistically significant (Chen et al, 1999). Another study of 2,812 elderly residents of New Haven, Connecticut observed that elevated levels of depression at baseline were associated with an increased risk of cognitive decline in those who were placed in the 'medium', as opposed to the 'high' category of cognitive functioning at baseline (Bassuk et al, 1998).…”
Section: Relationship Of Mdd To Admentioning
confidence: 90%
“…MDD has been identified both as a risk factor and a prodrome of Alzheimer's disease (AD) in clinical and community samples (Reding et al, 1985;Kral and Emery, 1989;Kokmen et al, 1991;Jorm et al, 1991;Alexopoulos et al, 1993b;Speck et al, 1995;Devanand et al, 1996;Henderson et al, 1997;Steffens et al, 1997;Bassuk et al, 1998;Chen et al, 1999;Yaffe et al, 1999;Geerlings et al, 2000;Jorm, 2000;Lockwood et al, 2000;Visser et al, 2000;Jorm, 2001;Lockwood et al, 2002;Wilson et al, 2002;Green et al, 2003;Sweet et al, 2004;Cannon-Spoor et al, 2005;Gatz et al, 2006;Rapp et al, 2006;Steffens et al, 2006). Community based studies have identified clinical depression, including depressive symptoms as a risk factor for the subsequent development of dementia.…”
Section: Relationship Of Mdd To Admentioning
confidence: 99%
“…Few studies determined that stress is major problem for later development of Alzheimer's disease [11,12]. While few researches explained that, psychosocial stress is not only a risk factor but it is the early symptom of Alzheimer's disease [13,14].…”
Section: Introductionmentioning
confidence: 99%